Civil sacred: the nobel and the laureate position in cultural space - Leypoldt, Günter (Poetics, 2023)
This essay situates the Nobel's institutional charisma within the “laureate position,” an older but still relevant socio-institutional formation that frames literature as a “higher good” (as distinct, say, from “mere” entertainment). The first three sections place the Nobel within the landscape of literary prizes, discussing its particular currency of value (strong rather than weak), its relation to different frames of value (consumerist, democratic, charismatic) and sites of consecration (the literary field vs. the civil-sphere). The next three sections sketch the Nobel's historical background - the laureate position - from the early modern period through the present, looking at how differing regimes (vocation, trade, singularity, communality) can form a “good match” depending on time and place. The final two sections explore how the Nobel deals with the prize system's internal tensions between “respect” and “esteem” (when identitarian expressivism clashes with notions of craft or intellectual mastery), as well as with tensions between competing agents of consecration (exploring how Handke's Nobel crystallizes a conflict between the more scholastic curation cultures of the laureate position and the media and problem brokers of the civil sphere).